Application of analogs of gonadotropinum-releasing hormone to girls with spontaneous sexual development, who suffer from the patients with Shereshevskii–Terner syndrome - Sprynchuk, N.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
This article presents the results of research on the assessment and the treatment of 70 children with Turner's syndrome. 38 girls had classic version karyotype — 45, XO and 32 children — mosaic forms. At 8 children from them, sexual development began without medicamental intervention. It is proved that the use of analogues of gonadotropin-releasing hormone in combination with growth hormone significantly improves the ultimate height of patients with independent activation of ovaries.